Table of Content - - (Journal of natural sciences, life and applied sciences, 2023)
Table of Content1. Natural factors and their impact on human securityDr. Salwa Hassan Ahmed2. The effects of climate change on water resources in north-eastern Morocco,  the case of Berkane cityDr. Mustapha Benasquar, Dr. Abdel Khalek Ghazi , Mr. Abdel Wahed Ahroud, Mr. Noureddine Buabid13. Afforestation targets according to remote sensing techniques and geographic information systems in Imam Turki bin Abdullah Royal Natural ReserveProf. Ahmed Abdullah Al-Dughairi4. The Effects of the Alternative Electrical Generators on Air, applied on Gaza CityDr. Hala Rezeq Al-Harazin5. The morphometric analysis of Al Nisr Valley Basin in Al Mithnab Governorate, in Kingdom of Saudi  Arabia, using remote sensing and the Geographic Information SystemDr. Wedad Hammdan Al-Ruqi6. Runoff hydrographs using Snyder and SCS synthetic unit hydrograph methods: A case study of ungauged watersheds of Imam Turki Bin Abdullah Royal Nature Reserve (ITBA) - Saudi ArabiaProf. Ahmed Abdullah Al-Dughairi
Keywords: Journal of Natural Sciences, Life and Applied Sciences